A mixed methods study of siblings' roles in maternal feeding practices in early childhood: an application of the learning from experience process - Cara F. Ruggiero; Amy M. Moore; Michele E. Marini; Stephen R. Kodish; Susan M. McHale; Jennifer S. Savage (BMC, 2022)
Abstract Background Firstborn children have higher rates of obesity compared to secondborns, perhaps due, in part, to differential feeding practices. Despite the centrality of siblings in family life and potential for influence, almost nothing is known about the role of siblings in parent feeding practices in early childhood. Methods Participants (n = 117) were mothers of consecutively born siblings. Firstborns participated in an RCT that compared a responsive parenting intervention designed for primary prevention of obesity against a safety control. Secondborns participated in an observational cohort. Multilevel models tested whether and how firstborn characteristics (temperament, appetite, rapid weight gain) at 16 weeks and 1 year were associated maternal feeding practices of secondborns in infancy at 16 weeks, 28 weeks, and 1 year (food to soothe) and at ages 1, 2, and 3 years (structure-and control-based feeding practices). A purposive subsample (n = 30) of mothers also participated in semi-structured interviews to further illuminate potential sibling influences on maternal feeding practices during infancy and toddlerhood. Results Firstborn characteristics did not predict secondborn feeding in infancy (all ps > 0.05). Firstborn negative affect, however, predicted mothers' less consistent mealtime routines (b (SE) = − 0.27 (0.09); p = 0.005) and more pressure (b (SE) = 0.38 (0.12); p = 0.001). Firstborn appetite predicted mothers' less frequent use of food to soothe (b (SE) = − 0.16 (0.07); p = 0.02) when secondborns were toddlers. Firstborn surgency, regulation, and rapid weight gain, however, did not predict secondborn feeding practices during toddlerhood (all ps > 0.05). Interviews with mothers revealed three ways that maternal experiences with firstborns informed feeding practices of secondborns: 1) Use of feeding practices with secondborn that worked for the firstborn; 2) Confidence came from firstborn feeding experiences making secondborn feeding less anxiety-provoking; and 3) Additional experiences with firstborn and other factors that contributed to secondborn feeding practices. Conclusions Some firstborn characteristics and maternal experiences with firstborns as well as maternal psychosocial factors may have implications for mothers' feeding practices with secondborns. Together, these mixed methods findings may inform future research and family-based interventions focused on maternal feeding of siblings in early childhood.